Nonfatal Hyperammonemic Encephalopathy as a Late Complication of Roux-en-Y Gastric Bypass - Juan D. Salcedo; Jordan S. Goldstein; Jose M. Quinonez; Maria Antonietta Mosetti (Case Reports in Gastrointestinal Medicine)
Roux-en-Y gastric bypass (RYGB) is the most common weight loss procedure performed in the US. Gastric bypass–related hyperammonemia (GaBHA) is a potentially fatal entity, characterized by encephalopathy associated with hyperammonemia and various nutritional deficiencies, which can present at variable time intervals after RYGB. Twenty-five cases of hyperammonemic encephalopathy after bariatric surgery have been previously reported in the literature. We describe the case of a 48-year-old Hispanic woman with no prior history of liver disease, presenting with nonfatal hyperammonemic encephalopathy as a late postoperative complication 20 years after undergoing a RYGB. Hyperammonemic encephalopathy in the absence of known hepatic dysfunction presents a diagnostic dilemma. An early diagnosis and intervention are crucial to decrease morbidity and mortality.